2023
DOI: 10.1073/pnas.2305756120
|View full text |Cite
|
Sign up to set email alerts
|

Causal ALS genes impact the MHC class II antigen presentation pathway

Binkai Chi,
Muhammet M. Öztürk,
Christina L. Paraggio
et al.

Abstract: Mutations in RNA/DNA-binding proteins cause amyotrophic lateral sclerosis (ALS), but the underlying disease mechanisms remain unclear. Here, we report that a set of ALS-associated proteins, namely FUS, EWSR1, TAF15, and MATR3, impact the expression of genes encoding the major histocompatibility complex II (MHC II) antigen presentation pathway. Both subunits of the MHC II heterodimer, HLA-DR, are down-regulated in ALS gene knockouts/knockdown in HeLa and human microglial cells, due to loss of the MHC II transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…However, the direct connection between genetic causes and the impaired immune system was still elusive. In this issue of PNAS, Chi et al reported that several ALS-associated RNA/DNA-binding proteins and C9ORF72 repeat expansion influence the gene expression of components in the major histocompatibility complex II (MHC-II) antigen presentation pathway ( 4 ). This possibly leads to immune system dysfunction which can contribute to neurodegeneration in ALS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direct connection between genetic causes and the impaired immune system was still elusive. In this issue of PNAS, Chi et al reported that several ALS-associated RNA/DNA-binding proteins and C9ORF72 repeat expansion influence the gene expression of components in the major histocompatibility complex II (MHC-II) antigen presentation pathway ( 4 ). This possibly leads to immune system dysfunction which can contribute to neurodegeneration in ALS.…”
mentioning
confidence: 99%
“…Many studies focused on their functions in neurons ( 18 ), although these proteins are expressed broadly in many cell types, including immune cells. In this work, Chi et al found that many immune-related proteins were down-regulated after knocking out FUS, TAF15, or MATR3 in HeLa cells using quantitative mass spectrometry analysis ( 4 ). Among the down-regulated genes affected by all the three RNA/DNA-binding proteins, a significant portion has functions related to antigen presentation.…”
mentioning
confidence: 99%